Using Silent Demonstration Acmethod to Improve Students’ Ability on Writing Procedure Text at the Seventh Grade of MTS DDI Pacongang Pinrang - Fusvita Sari (Universitas Sulawesi Barat, 2018)
: This research discussed are the use of silent demonstration method to improve the students ability in writing. This research is conducted using a quasi-experimental method was carried out. The population of the research was the Seventh grade of Mts DDI PacongangPinrang in academy years 2014- 2015 which consisted of two classes VII a and VII b were taken as the sample which consist of (30 students). The sample was drawn using cluster random sampling technique. While class VII B was chosen as the experimental group, while VII a was chosen as control group. The instrument for collecting data were writing test. The data obtained through the test were analyzed using t-test.The result of this research was use of silent demonstration significant difference with the use of conventional away / direct instruction (English book / script) of the students writing ability.This Indicate the mean the experimental group is higher than control group (75.8 > 68.83).There was also the result of t-test value is higher than t-table value (8.648 > 1.671) In other word hypothesis ) is that null hypothesis ( Ho) is rejected and Hypothesis Alternative (H1) is accepted. It is concluded ; the writing ability the seventh grade students of MTs DDI PacongangPinrang be improved through silent demonstration method by procedure text .